Development of an Occupational Risk Assessment Tool for Laboratory Animal Facilities. (June 2019) - Clayton, April M.; Hayes, James; Lathrop, George W.; Powell, Nathaniel
Introduction: Laboratory animal facilities aim to provide excellence in animal care and welfare and support scientific research. Critical to these goals is to ensure a safe work environment for personnel comprising veterinary and animal care, laboratory research, and maintenance staff. Objective: Thus, performing occupational risk assessments allows for evaluation of risks from identified hazards associated with a variety of tasks ongoing in laboratory animal facilities. Methods: Herein, we present the development of an occupational risk assessment tool purposed to capture the dynamics of work performed in laboratory animal facilities, calculate and prioritize identified risks associated with procedures and processes, and inform and evaluate risk mitigations. Results: We also discuss a risk assessment for refining sharps use in nonhuman primate husbandry and care to demonstrate the utility of this tool to improve occupational safety in our animal facility. Conclusion: This tool and framework evolve into a holistic occupational risk management system that identifies, evaluates, and mitigates occupational risks; determines risk acceptability; consistently ensures communication and consultation with frontline personnel, stakeholders, senior leadership, and subject matter experts in biosafety, science, and animal care and welfare; and continuously strives to improve and enhance the operations of laboratory animal facilities.